Analisis Kinerja Keuangan Perusahaan BUMN Sebelum dan Sesudah Privatisasi - Syadiah, Halimatus; Siswanto, Ely (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p10, 2022)
Privatization is one of the steps taken by State-Owned Enterprises (BUMN) in an effort to be able to compete and participate in capital market competition. The purpose of this study is to test whether there are differences in the financial performance of state-owned companies before and after privatization. The purposive sampling method was used in taking samples from BUMN that did privatization and had complete annual financial reports for a period of 3 years before and 3 years after privatization. Data analysis was carried out by analyzing descriptive statistics and inferential analysis which were tested by normality test and then hypothesis testing using STATAMP.15. The test results found that the Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover Ratio (TATO), Return on Equity (ROE) and Earning Per Share (EPS) had significant differences before and after privatization. Meanwhile Sales Growth (SG) did not find any difference before and after privatization. Keywords: BUMN; Privatization; Financial Performance; IPO.